Intertextuality is a Way for linking the imagined to the reference in the novel "The Pure Guardian Returns to his Stand Al-Zaki" by "Al-Tahir Watar". - benstiti, Sadia (Al-Adab Journal, 2020)
The Algerian writer "Taher Watar", in his novels, used to link the fictional text to the reference, using the technique of intertextuality. It shows the dialogue, interdependence and disharmony of cultures, thus holding as many texts as possible on their diversity and re-resurrecting them in the appropriate place, which fertilizes the current text and makes it more powerful and beautiful. But in his latest novel, "The Pure Guardian Returns to His Rightful Place", he employed him differently, as he relied on abstract narratives based on time, place and personnalities that are difficult to capture or identify; It imposed an imaginary space that we did not have in his earlier writings, and the way of linking the parts of the imagination. What is the intertextuality as a mechanism for linking the imagined and the reference? And how is the novelist's imagination stuck by intertextuality?